Kepemimipinan Transformasional Kepala Sekolah dalam Meningkatkan Profesionalisme Guru - Beni Habibi; Ira Maya Hapsari (Publikasi Indonesia, 2023)
The transnational headmasters' leadership is very much needed as a way to increase teacher professionalism with some of the efforts made by principals as leaders. This research approach is a qualitative case study type, data source that is, the principal as a source of informants supported by other sources. In this study, it can be concluded: 1) The strategy of the Head of SMP Negeri 1 Tegal City in improving teacher professionalism, is by conducting activities that lead to the development of quality teachers through teacher competency improvement programs, 2) Implementation of transformational leadership of principals in improving teacher professionalism in SMP Negeri 1 Tegal is implemented by influencing teachers and education personnel to carry out their duties according to the authority given. 3) Factors that support school principals in increasing teacher professionalism are by increasing teacher welfare and certification allowances, these are provided to motivate teachers to be able to improve the performance of educators and teachers. 4) Factors that inhibit the principal in improving teacher professionalism, the limited facilities that are able to support the implementation of the teaching and learning process, there are still teachers who have not maximized the tasks and responsibilities given.